Alberta First Nations Consultation & Accommodation Handbook – Updated to 2016 - Laidlaw, David (Canadian Institute of Resources Law, 2016)
This is an Update to our Alberta First Nations Consultation & Accommodation Handbook published on March 30, 2014 as CIRL Occasional Paper #44 (Handbook). This is an Update to our Alberta First Nations Consultation & Accommodation Handbook published on March 30, 2014 as CIRL Occasional Paper #44 (Handbook). The Handbook was a critical assessment of Alberta’s approach to satisfying the Crown’s duty to consult and accommodate aboriginal people in Alberta under The Government of Alberta’s Policy on Consultation with First Nations on Land and Natural Resource Management, 2013 (Consultation Policy). In the Handbook we reviewed the Consultation Policy, associated legislation and draft Corporate Guidelines as they existed at March 30, 2014. In this Update, we analyze the finalized guidelines, The Government of Alberta’s Guidelines on Consultation with First Nations on Land and Natural Resource Management (July 28, 2014) (Guidelines) together with relevant developments since March 30, 2014.